Parental responses to information about school quality: Evidence from linked survey and administrative data - Ellen Greaves; Iftikhar Hussain; Birgitta Rabe; Imran Rasul (University of Essex, Institute for Social and Economic Research (ISER), 2019)
Family and school based inputs determine children's cognitive achievement. We study the interaction between family and school inputs by identifying the causal impact of information about school quality on parental time investment into children. Our study context is England, where credible information on school quality is provided by a nationwide school inspection regime. Schools are inspected at short notice, with school ratings being based on hard and soft information. Such soft information is not necessarily known to parents ex ante, so inspection ratings can provide news to parents that plausibly shifts inputs into their children. We study this using household panel data linked to administrative records on school performance and inspection ratings. We observe some households being interviewed prior to their school being inspected (the control group), and others being interviewed post inspection (the treated group). Treatment assignment is thus determined by a household's survey date relative to the school inspection date. This assignment is shown to be as good as random. We use a forecast model to construct parental priors over school quality, and estimate heterogeneous treatment effects in response to good and bad news about school quality. We find that when parents receive good news they significantly decrease time investment into their children. This implies that for the average household, beliefs over school quality and parental inputs are substitutes. We go on to discuss insights our data and design provide on the nationwide inspections regime and: (i) its distributional impacts across households and schools; (ii) the impact it has on test scores through multiple margins of endogenous response of parents and children. Our findings highlight the importance of accounting for interlinked private responses by families to policy inputs into education.
Keywords: I20; I24; 330